Why Studying the Internationalization of Central and Eastern European (CEE) Organizations? A Theoretical Synopsis - Andreea MITAN; Elena-Mădălina VĂTĂMĂNESCU; Vlad-Andrei ALEXANDRU (Communications of International Proceedings, 2022)
The current paper intends to propose a theoretical synopsis of the main research directions which are worthy to be further developed via empirical investigations in a context-driven framework, namely the internationalization of Central and Eastern European (CEE) organizations. The conceptual approach addresses the pivotal lens through which the specificity of the CEE phenomena might be tackled (i.e., the institution-based approach) and the key research avenues regarding the internationalization of CEE organizations as fruitful prerequisites for theory development and / or extension. The present endeavor is designed as a preliminary outlook of the internationalization regional idiosyncrasies, thus calling for further and more in-depth dedicated analyses.
Keywords: Central and Eastern Europe (CEE); CEE organizations; internationalization; learning laboratory.